Effects of calcium aluminate cement on the acid resistance of metakaolin-based geopolymer. Issue 10 (5th March 2021) - Wu, Linping; Huang, Guangping; Liu, Wei Victor
Abstract : The aim of this study was to improve the acid resistance of a metakaolin-based geopolymer (MKG) by substituting metakaolin with calcium aluminate cement (CAC). The CAC was added at weight ratios of 5% and 10%. The raw materials were activated with a mixture of sodium hydroxide solution and sodium silicate solution. The cured MKG mortars were immersed in a sulfuric acid solution with a pH of 2 for 75 days. Tests for the volume of permeable voids, unconfined compressive strength (UCS) tests, thermogravimetric analysis and Fourier transform infrared spectroscopy were conducted before sulfuric acid immersion. It was found that the addition of CAC facilitated geopolymerisation and reduced the volume of permeable voids of the MKGs. Changes in UCS, ultrasonic pulse velocity, mass and length were monitored to evaluate acid resistance. It was found that the addition of CAC dramatically improved the acid resistance of the MKG due to the reduced volume of permeable voids and enhanced neutralisation capacity. The mixture with 10% CAC showed the lowest deterioration.